Deception in the Digital Age: Exploiting and Defending Human Targets Through Computer-Mediated Communications - Malin JD, Cissp; Gudaitis, Terry; Holt, Thomas; Kilger, Max (Elsevier Science & Technology, 2017)
Deception in the Digital Age: Exploiting and Defending Human Targets Through Computer-Mediated Communication guides readers through the fascinating history and principles of deception-and how these techniques and stratagems are now being effectively used by cyber attackers. Users will find an in-depth guide that provides valuable insights into the cognitive, sensory and narrative bases of misdirection, used to shape the targeted audience's perceptions and beliefs. The text provides a detailed analysis of the psychological, sensory, sociological, and technical precepts that reveal predictors of attacks-and conversely postmortem insight about attackers-presenting a unique resource that empowers readers to observe, understand and protect against cyber deception tactics. Written by information security experts with real-world investigative experience, the text is the most instructional book available on the subject, providing practical guidance to readers with rich literature references, diagrams and examples that enhance the learning process.